Socialism and Bureaucracy - Andrejauskas, Vladas (Problemos, 1990)
In the paper an attempt is made to explain the possibility of bureaucracy in socialism. The origin and main features of bureaucracy as well as the causes of its establishment into the system of state control after the socialist revolution are analysed. It is said that from the theoretical point of view the chances of socialism to overcome bureaucracy are greater than those of capitalism. However, in practice the situation is reverse. Finally, the inference is drawn that the guarantees should be created to restrict bureaucracy in socialism.